Analisis Faktor Risiko Terjadinya Stroke Serta Tipe Stroke - Trio Gustin Rahayu (Faletehan Health Journal, 2023)
Stroke is a disease caused by an impaired blood flow to the brain that can cause death. The risk factors of stroke can be divided into modifiable factors and non-modifiable factors. Stroke prevention can be done by avoiding modifiable risk factors. This research used a retrospective method and a total sampling technique of 200 stroke patients as the respondents. The data was taken from their medical record document at the Tulip Room of Doctor Dradjat Prawiranegara Hospital from January to March 2020. The data were analyzed by a descriptive approach which described the variables of age, sex, type of stroke (ischemic or hemorrhagic), and history of disease (hypertension, DM, and cholesterol) in-depth. The variables were considered as modifiable and non-modifiable risk factors. The risk factors in this study were determined based on the medical record data which showed the highest number. The results of this study indicated that most of the respondents experienced ischemic stroke. In addition, the most non-modifiable stroke risk factors were age > 50 years and male sex. Meanwhile, the modifiable stroke risk factor showing the highest percentage was hypertension. It was the main cause of intracerebral hemorrhage, more than 60% of stroke patients suffered from it. Further research should more emphasize on the relationship analysis of risk factors and stroke occurrence.